On the centre-focus problem in some Liénard systems - Mencinger, Matej (JET on-line, 2017)
A large family of planar systems of ODEs arising from Liénard equations is considered. A Liénard equation is commonly used in practical problems, in particular in (electro)mechanics.
Keywords: center-focus problem; complex behavior; diferencialne enačbe; elektromehanika; Liénardova enačba; matematika; polinomialni sistem; polynomial system of ODEs; razmeščanje centrov